2020
DOI: 10.3390/su12229775
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Approach to Understand the Mobility Patterns of the Portuguese Population during the COVID-19 Pandemic

Abstract: SARS-CoV-2 emerged in late 2019. Since then, it has spread to several countries, becoming classified as a pandemic. So far, there is no definitive treatment or vaccine, so the best solution is to prevent transmission between individuals through social distancing. However, it is not easy to measure the effectiveness of these distance measures. Therefore, this study uses data from Google COVID-19 Community Mobility Reports to understand the Portuguese population’s mobility patterns during the COVID-19 pandemic. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 22 publications
3
40
0
1
Order By: Relevance
“…As the framework uses the first seven days for the calculation and the first case of COVID-19 in Portugal was on 3 March 2020, the results for Rt are from 10 March 2020 through 9 March 2021. According to [9], at the beginning of the pandemic, transmission occurred exponentially, with Rt greater than 3. With the rapid response of the Portuguese government, this value quickly dropped to less than 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the framework uses the first seven days for the calculation and the first case of COVID-19 in Portugal was on 3 March 2020, the results for Rt are from 10 March 2020 through 9 March 2021. According to [9], at the beginning of the pandemic, transmission occurred exponentially, with Rt greater than 3. With the rapid response of the Portuguese government, this value quickly dropped to less than 1.…”
Section: Resultsmentioning
confidence: 99%
“…These values are anonymous and represent a portion of the population. Thus, it is considered that if the population decreases its presence in parks, restaurants, transport hubs, among others, the number of risk contacts will drop [9].…”
Section: Methodsmentioning
confidence: 99%
“…The COVID-19 pandemic has had a major impact on the public passenger transport system [10], as it was identified as a high-risk environment for the spread of the virus [11][12][13][14]. Compared to private vehicles and other modes of transport [15][16][17], public transport was the most strongly affected [5,6,17,18], since conducting social distancing and providing the necessary materials for safe travel required a great deal of material and organizational resources [18].…”
Section: Transport and Covid-19mentioning
confidence: 99%
“…At the beginning of December 2019, a new coronavirus disease (COVID-19) ap-peared in the city of Wuhan, which then quickly spread to China and almost all coun-tries of the world [1][2][3][4][5][6][7]. Some studies have shown that the number of infections and deaths continues to increase, which has posed major public health and governance concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Under the concept of people-oriented urban design [ 1 ], the interaction between human behavior and urban material space is the most important dimension to study the regulation of urban processes [ 2 , 3 , 4 , 5 , 6 ]. Urban population distribution [ 7 , 8 , 9 ], like population activity density [ 10 ] and urban vitality distribution [ 11 ], is the dependent variable of urban spatial behavior that can be used to characterize the operational state of an urban area [ 12 ].…”
Section: Introductionmentioning
confidence: 99%